Model predictive controlled application of power management algorithm for battery energy storage system providing frequency ancillary service - AKPINAR, KÜBRA NUR (My University, 2023)
The active power that must be provided in accordance with frequency ancillary service regulations when battery energy storage systems participate in the frequency ancillary service is modelled in this study using a Model Predicted Controlled (MPC) 2-Level Voltage Source Converter (2L-VSC). The reference active power for the 2 MW battery energy storage system was determined using the rule-based power management method, and the outcome was then used as the Model Predicted Control\"s input data. The output power for the MPC 2L-VSC, whose simulation study was conducted in the Simulink, successfully remained within the active power-frequency envelope in the frequency ancillary service regulation, and the demanded power was delivered by using the battery state of charge (SOC) value optimally.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Sinyal İşleme; Bilgisayar Bilimleri; Algoritmalar; Matematik; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Control and System Engineering; Signal Processing; Computer Sciences; algorithms; Mathematics; Computer Science; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Bilgisayar Bilimi; Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; BİLGİSAYAR BİLİMİ, YAPAY ZEKA; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; MATEMATİK, UYGULAMALI; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); COMPUTER SCIENCE; ENGINEERING; MATHEMATICS; AUTOMATION & CONTROL SYSTEMS; COMPUTER SCIENCE, ARTIFICIAL INTELLIGENCE; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; MATHEMATICS, APPLIED; ENGINEERING, MANUFACTURING; Enerji Mühendisliği ve Güç Teknolojisi; Fizik Bilimleri; Elektrik ve Elektronik Mühendisliği; Emniyet, Risk, Güvenilirlik ve Kalite; Yapay Zeka; Bilgisayar Bilimi Uygulamaları; Kontrol ve Optimizasyon; Modelleme ve Simülasyon; Energy Engineering and Power Technology; Physical Sciences; Electrical and Electronic Engineering; Safety, Risk, Reliability and Quality; Artificial Intelligence; Computer Science Applications; Control and Optimization; Modeling and Simulation